Structural Insights into the HWE Histidine Kinase Family: The Brucella Blue Light-Activated Histidine Kinase Domain. Issue 6 (27th March 2016) - Rinaldi, Jimena; Arrar, Mehrnoosh; Sycz, Gabriela; Cerutti, María Laura; Berguer, Paula M.; Paris, Gastón; Estrín, Darío Ariel; Martí, Marcelo Adrián; Klinke, Sebastián; Goldbaum, Fernando Alberto
Abstract: In response to light, as part of a two-component system, the Brucella blue light-activated histidine kinase (LOV-HK) increases its autophosphorylation, modulating the virulence of this microorganism. The Brucella histidine kinase (HK) domain belongs to the HWE family, for which there is no structural information. The HWE family is exclusively present in proteobacteria and usually coupled to a wide diversity of light sensor domains. This work reports the crystal structure of the Brucella HK domain, which presents two different dimeric assemblies in the asymmetric unit: one similar to the already described canonical parallel homodimers (C) and the other, an antiparallel non-canonical (NC) dimer, each with distinct relative subdomain orientations and dimerization interfaces. Contrary to these crystallographic structures and unlike other HKs, in solution, the Brucella HK domain is monomeric and still active, showing an astonishing instability of the dimeric interface. Despite this instability, using cross-linking experiments, we show that the C dimer is the functionally relevant species. Mutational analysis demonstrates that the autophosphorylation activity occurs in cis . The different relative subdomain orientations observed for the NC and C states highlight the large conformational flexibility of the HK domain. Through the analysis of these alternative conformations by means of molecular dynamics simulations, we also propose a catalytic mechanism for Brucella LOV-HK. Graphical Abstract: Highlights: The crystal structure of the Brucella HK domain reveals two distinct dimers. In solution, the Brucella HK domain is an active monomer. The canonical dimer is the functionally relevant species. The autophosphorylation occurs in cis . A catalytic mechanism for Brucella LOV-HK is proposed.